2023
DOI: 10.1111/bcpt.13857
|View full text |Cite
|
Sign up to set email alerts
|

Reasons why older adults in three countries agreed with a deprescribing recommendation in a hypothetical vignette

Abstract: The purpose of this study was to examine factors important to older adults who agreed with a deprescribing recommendation given by a general practitioner (GP) to a hypothetical patient experiencing polypharmacy. We conducted an online, vignette‐based, experimental study in the United Kingdom, United States and Australia with participants ≥65 years. The primary outcome was an agreement with a deprescribing recommendation (6‐point Likert scale; 1 = strongly disagree and 6 = strongly agree). We performed a conten… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…Other studies using the rPATD have shown substantial differences (30%–73% gap) between these questions with the global question responses always higher8 39–43 suggesting the influence of the doctor should not be underestimated. Similarly, a content analysis including over 2500 participants from Australia, the UK and the USA found that approximately one-half of older adults who agreed with deprescribing in a hypothetical scenario felt that the doctor’s recommendation was an important consideration 44…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies using the rPATD have shown substantial differences (30%–73% gap) between these questions with the global question responses always higher8 39–43 suggesting the influence of the doctor should not be underestimated. Similarly, a content analysis including over 2500 participants from Australia, the UK and the USA found that approximately one-half of older adults who agreed with deprescribing in a hypothetical scenario felt that the doctor’s recommendation was an important consideration 44…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a content analysis including over 2500 participants from Australia, the UK and the USA found that approximately one-half of older adults who agreed with deprescribing in a hypothetical scenario felt that the doctor’s recommendation was an important consideration. 44 …”
Section: Discussionmentioning
confidence: 99%
“…The primary outcome was the attitudes, beliefs, fears, and recommended actions of participants in response to the recommendation of deprescribing. The reasons participants agreed and disagreed were substantially different thematically and conceptually; therefore, a content analysis of the responses of participants who agreed (English text only) was conducted separately …”
Section: Methodsmentioning
confidence: 99%
“…As we embark on the new year, we invite you to explore the wealth of knowledge and exciting content our journal offers. In 2023, we published three Special Collections from focused conferences supported by the Nordic Association for the Publication of Basic and Clinical Pharmacology and Toxicology, including Adhesion G‐Protein‐coupled Receptors, 1–10 Transmembrane Transporter Proteins: Catching Transport in Motion 11–19 and Advancing Deprescribing: Learnings from the first International Conference on Deprescribing 20–31 . The second part of the latter Special Collection will appear in the January 2024 issue.…”
mentioning
confidence: 99%